Matrix of risk factors for railway construction projects . - Jan Kowalski; Marzena Lendo-Siwicka (Acta Scientiarum Polonorum. Architectura)
The article presents main assumptions of an original method for scheduling railway investments in Poland, taking into account the risk factors during their implementation. The risk factors were identified by the authors during extensive research and analysis. Based on the proposed method, a future user will be able to determine the most likely cost and duration of a planned investment. The article also presents the implementation of the method in a real investment process (construction project) in terms of its implementation time. When designing the method, it was assumed that the method which is not complicated to implement and is supported by an appropriate computational program will motivate teams planning railway projects to implement them in real implementation processes and increase the credibility of their schedules.